2005
DOI: 10.1007/s00253-005-0202-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bordetella pertussis growing as biofilm by chemical analysis and FT-IR spectroscopy

Abstract: Although Bordetella pertussis, the etiologic agent of whooping cough, adheres and grows on the ciliated epithelium of the respiratory tract, it has been extensively studied only in liquid cultures. In this work, the phenotypic expression of B. pertussis in biofilm growth is described as a first approximation of events that may occur in the colonization of the host. The biofilm developed on polypropylene beads was monitored by chemical methods and Fourier transform infrared (FT-IR) spectroscopy. Analysis of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 70 publications
4
75
0
3
Order By: Relevance
“…Biofilms were grown on flat polypropylene beads (300 g; f = 4.2 mm, h = 1.5 mm, with an average density of 0.901 g/cm 3 , Petroken, Argentina) in glass column reactors (f = 6 cm, h = 45 cm, IVA SA, Argentina). Experiments were carried out essentially as described previously by Bosch et al [21]. Briefly, a planktonic culture of B. pertussis (200 mL, OD 650 = 1.0) grown in SS broth was used as inoculum for each column and incubated for 5 h at 377C to allow cell attachment to the beads.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms were grown on flat polypropylene beads (300 g; f = 4.2 mm, h = 1.5 mm, with an average density of 0.901 g/cm 3 , Petroken, Argentina) in glass column reactors (f = 6 cm, h = 45 cm, IVA SA, Argentina). Experiments were carried out essentially as described previously by Bosch et al [21]. Briefly, a planktonic culture of B. pertussis (200 mL, OD 650 = 1.0) grown in SS broth was used as inoculum for each column and incubated for 5 h at 377C to allow cell attachment to the beads.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…In B. pertussis physiologic and pathogenic aspects have been extensively studied focusing on the planktonic mode of growth, while only a few works so far have considered the biofilm lifestyle of this bacterial pathogen [2,[20][21][22]. Therefore, generally only limited data is available on the nature of B. pertussis biofilm and information on a proteomic level is completely missing.…”
Section: Introductionmentioning
confidence: 99%
“…In a proposed translational application we hope to identify not only the presence or absence of bacteria but also to identify a particular strain thus increasing the importance of improving Type II error. Previous studies have used spectroscopy to analyze biologic specimens [2,10,12,18,21]. Ngo-Thi et al [18] reported the ability of conventional FT-NIR spectroscopy in the MIR region and multivariate data analysis to correctly classify different nonbiofilm-associated bacteria in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we asked: (1) Can principal component analysis differentiate the spectral curves for biofilm obtained from Staphylococcus aureua, Staphylococcus epidermidis, and Pseudomonas aeruginosa? (2) What is the accuracy of FT-NIR/multivariate data analysis in identifying the specific species associated with biofilm?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation